Development and Psychometric Validation of Tinnitus Qualities and Impact Questionnaire - Vinaya Manchaiah; Gerhard Andersson; Eldré W. Beukes; Marc A. Fagelson; De Wet Swanepoel; Eithne Heffernan; David Maidment (Clinics and Practice)
Background: To develop and validate the Tinnitus Qualities and Impact Questionnaire (TQIQ), a new tool for evaluating the perceived qualities of tinnitus sound. Method: The study was part of two clinical trials on internet-based tinnitus interventions, using cross-sectional (n = 380) and pretest–posttest data (n = 280). Participants completed various questionnaires online, including the newly developed TQIQ and measures of tinnitus severity (Tinnitus Functional Index; TFI), anxiety (Generalized Anxiety Disorder 7; GAD-7), depression (Patient Health Questionnaire 9; PHQ-9), insomnia (Insomnia Severity Index; ISI), and health-related quality of life (EQ-5D-5L Visual Analog Scale; VAS). The psychometric properties of the TQIQ were assessed, including construct validity, internal consistency reliability, floor and ceiling effects, interpretability, and responsiveness to treatment. Results: Exploratory factor analysis resulted in two factors that accounted for 57% of the variance—internal and external tinnitus qualities. Overall, 92% convergent validity predictions were confirmed; TQIQ total scores strongly (≥0.6) or moderately (0.30 to 0.59) correlated with the TFI, GAD-7, PHQ-9, and ISI. The known-groups validity prediction was confirmed as individuals with an overall TFI score > 50 (severe) obtained significantly higher TQIQ scores. All internal consistency reliability statistics were within the required range (Cronbach’s α > 0.8). Floor and ceiling effects were negligible. ROC established clinically important cut-off scores, enhancing the interpretability of tinnitus severity classification. Finally, 89% convergent validity predictions were confirmed; TQIQ and TFI change scores were moderately correlated, indicating good responsiveness of the former to treatment. Conclusions: The TQIQ has adequate psychometric properties, providing a standardized measure for the assessment of characteristics of tinnitus sound in clinical practice.